2010
DOI: 10.1111/j.1551-2916.2010.04210.x
|View full text |Cite
|
Sign up to set email alerts
|

Electric Current Activation of Sintering: A Review of the Pulsed Electric Current Sintering Process

Abstract: The phenomenal increase during the past decade in research utilizing pulsed electric current to activate sintering is attributed generally to the intrinsic advantages of the method relative to conventional sintering methods and to the observations of the enhanced properties of materials consolidated by this method. This review focuses on the fundamental aspects of the process, discussing the reported observations and simulation studies in terms of the basic aspects of the process and identifying the intrinsic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
238
0
9

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 583 publications
(248 citation statements)
references
References 135 publications
1
238
0
9
Order By: Relevance
“…[36][37][38] In addition, the applied current can enhance sintering via non-thermal effects, such as enhanced defect mobility, point defect generation and electromigration. 39 It is worth pointing out that the improved densification behaviour of SPS over HP has also been reported for commercially pure Ti powder. 40 It has been shown that SPS can result in dense Ti bodies at 730uC, while the same Ti powder would require 950uC to become dense bodies by using HP.…”
Section: Densification Enhancement Through Spsmentioning
confidence: 99%
“…[36][37][38] In addition, the applied current can enhance sintering via non-thermal effects, such as enhanced defect mobility, point defect generation and electromigration. 39 It is worth pointing out that the improved densification behaviour of SPS over HP has also been reported for commercially pure Ti powder. 40 It has been shown that SPS can result in dense Ti bodies at 730uC, while the same Ti powder would require 950uC to become dense bodies by using HP.…”
Section: Densification Enhancement Through Spsmentioning
confidence: 99%
“…This high energy induces the formation of sintering neck at an early stage of densification (first sintering step) between adjacent grains [24,25]. This can produce a larger grain size, compared to the microwave technique, in the final stage of sintering.…”
Section: Fig 3 Represents the Fe-sem Fracture Surface Of Las Samplesmentioning
confidence: 99%
“…М.А.Ла вренть ева СО РА Н на ус та новке Sinter Land Labox 1 575. Основным отличием метода SPS от т ра диционного прессова ни я в порошковой мета ллургии является прило жение элек т рическ их импульсов непос ре д ственно к образцу, что способствует быстрому на г реву и сох ра нению мик рос т ру к т у рны х параметров порошка в консолидированном материале [7][8][9][10][11][12].…”
Section: The Methods Of Obtaining Nanoporous Ceramicsunclassified